2016
DOI: 10.3892/mmr.2016.5342
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 enhances osteogenic differentiation of bone marrow mesenchymal stem cells in ovariectomized rats

Abstract: Sphingosine-1-phosphate and its structural analog FTY720 (fingolimod) are important in the inhibition of osteoclast differentiation and bone resorption, however, it remains unknown whether they enhance osteogenic differentiation of the bone marrow mesenchymal stem cells (BM‑MSCs). The present study investigated the effect of FTY720 on the osteogenic differentiation of BM‑MSCs from the femurs of the ovariectomized (OVX) rats. Three different concentrations (1, 10 and 100 nM) of FTY720 were demonstrated to marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
(39 reference statements)
2
3
0
Order By: Relevance
“…The S1Pr1 agonist, FTY720, is a S1P analog approved by the U.S. Food and Drug Administration (FDA) for the treatment of oral diseases and multiple sclerosis. Previous reports showed that locally‐delivered FTY720 could increase bone volume in cranial defects 25,46,47 . In this study, the locally delivered FTY720 loaded in a PEG gel (also FDA approved) promoted bone regeneration by significantly increasing the number of osteoblasts and volume of Type H vessels, which was similar to the beneficial effect of the controlled mechanical loading.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The S1Pr1 agonist, FTY720, is a S1P analog approved by the U.S. Food and Drug Administration (FDA) for the treatment of oral diseases and multiple sclerosis. Previous reports showed that locally‐delivered FTY720 could increase bone volume in cranial defects 25,46,47 . In this study, the locally delivered FTY720 loaded in a PEG gel (also FDA approved) promoted bone regeneration by significantly increasing the number of osteoblasts and volume of Type H vessels, which was similar to the beneficial effect of the controlled mechanical loading.…”
Section: Discussionsupporting
confidence: 65%
“…Previous reports showed that locally-delivered FTY720 could increase bone volume in cranial defects. 25,46,47 In this study, the locally delivered FTY720 loaded in a PEG gel (also FDA approved) promoted bone regeneration by significantly increasing the number of osteoblasts and volume of Type H vessels, which was similar to the beneficial effect of the controlled mechanical loading. Additionally, activating S1Pr1 did not directly affect the maturation of osteoprogenitors in vitro, suggesting that S1Pr1 agonistinduced beneficial effect in bone regeneration is mediated mainly by endothelial cells.…”
Section: Discussionsupporting
confidence: 52%
“…There are S1P-targeted therapeutic approaches for osteoporosis using S1P lyase inhibitors (e.g., CYM5520 and LX2931) and a structural analog of sphingosine (e.g., FTY720, fingolimod) (Tian et al, 2021). These pharmacological treatments increase S1P at tissue levels, inducing new bone formation, which was confirmed in ovariectomized mice and rat studies (Huang et al, 2016;Weske et al, 2019). Currently, however, it remains unclear whether the expression of S1P receptors in osteocytes has a key regulatory role in response to S1P in the blood, and therefore further studies are required.…”
Section: Sphingolipid Signaling Pathwaymentioning
confidence: 84%
“…S1PR/S1P has been shown to be important for osteoclast formation, bone cells that break down bone tissue. A few recent studies have demonstrated that FTY720 binding to S1PR 1 and or S1PR 2 prevents osteoclast formation [258, 259]. By blocking osteoclast formation and reducing bone loss, FTY720 may indirectly have added benefits for advanced cancers that migrate to the bone and where metastasis involves considerable osteolysis [260].…”
Section: S1pr Expression and Malignancymentioning
confidence: 99%